The Na+/glucose cotransporters: from genes to therapy - Sabino-Silva,R. (2010)
Glucose enters eukaryotic cells via two types of membrane-associated carrier proteins, the Na+/glucose cotransporters (SGLT) and the facilitative glucose transporters (GLUT). The SGLT family consists of six members. Among them, the SGLT1 and SGLT2 proteins, encoded by the solute carrier genes SLC5A1 and SLC5A2, respectively, are believed to be the most important ones and have been extensively explored in studies focusing on glucose fluxes under both physiological and pathological conditions. This review considers the regulation of the expression of the SGLT promoted by protein kinases and transcription factors, as well as the alterations determined by diets of different compositions and by pathologies such as diabetes. It also considers congenital defects of sugar metabolism caused by aberrant expression of the SGLT1 in glucose-galactose malabsorption and the SGLT2 in familial renal glycosuria. Finally, it covers some pharmacological compounds that are being currently studied focusing on the interest of controlling glycemia by antagonizing SGLT in renal and intestinal tissues.